Life and death at Dmanisi, Georgia: Taphonomic signals from the fossil mammals. Issue 171 (October 2022) - Tappen, Martha; Bukhsianidze, Maia; Ferring, Reid; Coil, Reed; Lordkipanidze, David
Abstract: There are many hypotheses regarding influences on the early hominin biogeographic spread into Eurasia; among them is increased meat-eating. Dmanisi in Georgia is one of the rare Early Pleistocene sites in Eurasia, and here we present primary information and analysis of the medium and large mammal taphonomy, contributing information about site formation and the hominins' interaction with the fauna. Nearly 85% of the specimens come from the B1 stratum. Relative abundances of mammal families demonstrate some bias toward carnivores, especially Canis borjgali, and diverse Felidae species. Bones display little weathering. Post-depositional surface modifications and matrix obscure many bone surfaces, but carnivore tooth marking is the most common bone surface modification from the nutritive taphonomic phase. Tooth pits are large, in the size range of those made by modern Crocuta crocuta and Panthera leo. Breakage variables indicate most breaks occurred while the bones were still fresh, many by carnivore consumption. Fairly even limb bone representation of herbivores suggests carcasses were introduced to the site nearly whole. Hominin tool marks are present in low frequencies, but they suggest a variety of behaviors. These marks are found on Equus, Palaeotragus, Bison, large cervids, Pseudodama, Canis, and Mammuthus. Some were made by filleting proximal limb segments, and so are likely indicative of early access to carcasses, while other marks suggest scavenging. The Homo taphonomic variables resemble the rest of the taphonomic signatures from the site with little weathering, a slightly higher percentage of their bones are whole, but only a few have probable carnivore damage. The assemblage characteristics are compared to modern actualistic and experimental assemblages, and it is concluded that Dmanisi presents a palimpsest of hyena denning, felid activity, hominin meat-eating and likely natural deaths.